Research of electrodynamic characteristics CH-based accelerating structures - Kalashnikova, A.A.; Lalayan, M.V.; Toporkov, S.E. (Вопросы атомной науки и техники, 2013)
The CH-based accelerating structure for linear proton accelerator is considered in the paper. The electrodynamic characteristics structures with different geometries are compared. They are the structure with a variable cavity diameter and the structure with pylons. The models have 7 gap CH-based structure with end drift tubes modified geometry. Structure is tuned to the operating frequency 352 MHz and the relative phase beam velocity β = 0.1. The geometric dimensions influence on the overvoltage field factor and electrodynamic characteristics are investigated. The electrodynamic characteristics such as shunt impedance per unit length, Q factor and TOF factor are considered. Field distribution along the axis of the structures is configured to unevenness less than 5%. Also the results of focused beam dynamics simulation are presented in the paper. The structure is proposed to operate at single bunch mode. Bunch current is 10 mA.